2005
DOI: 10.1111/j.1469-8137.2005.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptome of Populus in elevated CO2

Abstract: Summary• The consequences of increasing atmospheric carbon dioxide for long-term adaptation of forest ecosystems remain uncertain, with virtually no studies undertaken at the genetic level. A global analysis using cDNA microarrays was conducted following 6 yr exposure of Populus × euramericana (clone I-214) to elevated [CO 2 ] in a FACE (free-air CO 2 enrichment) experiment.• Gene expression was sensitive to elevated [CO 2 ] but the response depended on the developmental age of the leaves, and < 50 transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 57 publications
6
101
0
Order By: Relevance
“…The POP2 Populus glass-spotted cDNA microarrays were used for this study (http://www.populus.db.umu.se) and hybridized in an automated slide processor (Lucidea ASP Hybridization Station; Ge-Healthcare) as described by Taylor et al (2005) according to an all pairwise-comparison design (see Supplemental Figure 2 online). A dye-swap replication was done for each hybridization.…”
Section: Microarray Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The POP2 Populus glass-spotted cDNA microarrays were used for this study (http://www.populus.db.umu.se) and hybridized in an automated slide processor (Lucidea ASP Hybridization Station; Ge-Healthcare) as described by Taylor et al (2005) according to an all pairwise-comparison design (see Supplemental Figure 2 online). A dye-swap replication was done for each hybridization.…”
Section: Microarray Analysesmentioning
confidence: 99%
“…cDNA was synthesized as described (Taylor et al, 2005) with slight modifications: 30 mg of total RNA and 1 mL oligo(dT) anchor (5 mg/mL; TTTTTTTTTTTTTTTTTTTTVN) in a volume of 10 mL was incubated at 708C for 5 min and subsequently chilled on ice. First-strand synthesis was done in reverse transcriptase buffer (Invitrogen), 0.6 mL aa-dUTP/dNTP mix (500 mM of dATP, dCTP, dGTP, 100 mM dTTP, and 400 mM aa-dUTP; Sigma-Aldrich), 1 mM DTT, 30 units of RNase inhibitor (Invitrogen), and 200 units of Superscript II RNase H À reverse transcriptase (Invitrogen) in a total volume of 30 mL.…”
Section: Microarray Analysesmentioning
confidence: 99%
“…Transcript analysis of growing poplar (Populus spp.) leaves exposed to elevated [CO 2 ] showed that genes involved in cell wall loosening and synthesis were up-regulated (Taylor et al, 2005;Druart et al, 2006). Therefore, at least in poplar, elevated [CO 2 ] appears to stimulate or prolong expansion in leaves (Ferris et al, 2001;Taylor et al, 2003;Druart et al, 2006).…”
mentioning
confidence: 99%
“…Microarray analysis was conducted, and real time PCR was run to verify microarray analyses. Early results from this work allowed us to compared CO 2 -responsive and CO 2 -nonresponsive clones (Taylor et al 2005, Rae et al 2007). …”
Section: Background Methods and Activitiesmentioning
confidence: 99%
“…The combined treatment of +CO 2 +O 3 resulted in the differential expression of genes that were not up-regulated with individual gas treatments. Taylor et al (2005) used cDNA microarrays for Populus euramericana (clone I-214) that had received 6 years of elevated CO 2 to study long-term changes in genetic expression in response to elevated CO 2 . They found gene expression was sensitive to elevated CO 2 , but the response depended on the developmental age of the leaves.…”
Section: Popgenics Funding Helped Gupta Et Al (2005) Complete Publicmentioning
confidence: 99%